Horizontal kiln for drying recovered particulate plastics - of simple design to permit economic recovery (1976)
Recovery of powdered or granular plastics materials contaminated by damp or other materials by passing the material into a slightly inclined horizontal rotary kiln which is purged by air heated to 130-160 degrees C and passed countercurrent through a coaxial tube perforated to release the hot air uniformly along the length of the kiln. The dried materials are subsequently passed through an automatic sieve. The equipment is of simple construction and allows material to be recovered at an economic cost: the design avoids the need for close temp control and associated sophisticated equipment.